Dari Kristopraksis ke Antropopraksis: Inkarnasi, Sejarah, dan Menjadi Manusia melalui Lensa Kaum Miskin dalam Teologi Ignacio Ellacuría, S.J. dan Daniel Lucas Lukito - Sasongko, Nindyo (Veritas : Jurnal Teologi dan Pelayanan, 2024)
The purpose of this article is to relate the incarnation, the cross, and what it means to be human in the struggle for justice. Amid the suspicions of some U.S. theologians against the use of Marxist derivative theories, this article argues otherwise. Christian theology can be enriched by these theories, even if they seem to contradict certain Christian interpretations. This is due to the interdisciplinary nature of theology which is always in dialogue with different scientific disciplines. By focusing on the doctrines of the incarnation and the cross in the theology of Ignacio Ellacuría, S.J. and Daniel Lucas Lukito, this article shows that Christian theologians can use non-Christian concepts, including those of Marxist thinkers, to build contextual theology. Firstly, it will be shown how contemporary thinkers discuss the nexus between incarnation, the cross, and history especially in the thought of Slavoj Žižek, Jürgen Moltmann, and Eberhard Jüngel who were influenced by Hegel and the social theory of Marxism. Then, this article will expound how Ellacuría and Lukito take the Marxist vocabulary and intertwine it with the doctrine of the incarnation, the cross, and history. If the crucified Jesus in history unites with the poor then, in the last part, humanity is not only defined in Christ, but Christ is also defined in crucified humanity, which I call “anthropopraxis.”